WEB BASED VIRTUAL ROBOT PROTOTYPING AND MANUFACTURING - Mihali, Raul; Sobh, Tarek; Koval, Vasyl; Korkishko, Tymur; Sachenko, Anatoly; Kochan, Volodymyr (International Journal of Computing, 2002)
Developing an environment that enables optimal and flexible design of robot manipulators using universal reconfigurable links, joints, controllers, actuators and sensors is an essential step for efficient robot design and prototyping. Robot control has to be made by a universal controller with remote hardware and software reconfigurations. This technique allows to create an optimal configuration of software and hardware components for designing of the specialized robot, its algorithmic control and rapid prototyping.